For the greater good : resolving differences in opinions on the standard indigenous language in Sabah - Jeannet Stephen,; Rosazman Hussin,; Rosy Talin,; Reany Koton, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Bahasa Kadazandusun or BKD is the sole indigenous language offered in schools in Sabah, initially under the Pupils’ Own Language (POL) program based on the Education Act 1966. Different reactions towards BKD come from various concerned stakeholders i.e., ethnic societies, cultural bodies, and political organizations within the Kadazan and Dusun Orang Asal communities that make up almost 30% of the population of Sabah. Views on BKD range from critical and hardline positions to support and tolerance. Differing opinions can be read in the media due to the press statements by organizations or individuals reported in the news. However, one group whose opinions are rarely heard within the debates is the Orang Asal parents whose children are BKD learners at schools. This paper extracts findings from a larger study conducted to investigate the views and perspectives of stakeholders on the teaching and learning of the Kadazandusun language. In particular, this paper discusses relevant extracts from focus group discussions specifically with parents (n = 294) from five districts (Tambunan, Keningau, Kudat, Kota Marudu, and Tuaran). The study found that Orang Asal parents who are non-Kadazan or non-Dusun speakers are supportive of the BKD’s position and role as the sole indigenous language option taught in the national education system while recognizing that they want their indigenous languages to be transmitted to their younger generation, the parents also strongly encourage for inclusion of other ethnic languages in the system, formally or informally. This study found that the acceptance and tolerance shown by the parents, though themselves not speakers of Kadazandusun, are consistent with the sense of community present within indigenous communities in Sabah. The support given by non-Kadazandusun speakers to the standard language points to existing social harmony in a multicultural and multilingual society in Sabah. This paper also discusses at length the history behind the establishment of BKD and language standardization ideology within indigenous communities’ context.